Envy theory : perspectives on the psychology of envy - Ninivaggi, Frank John (Rowman & Littlefield Publishers, 2010)
"Envy arouses questions about fairness and unequal distribution of resources. Scavenging for hidden treasures and exploiting the acquisition of what is perceived to be free also imply underlying envy and greed. Envy, in isolation, can be destructive to psychological processes. Endowments of envy, however, are not as bleak and unsparing as they at first may appear. Envy, recognized and intelligently managed, transforms and may spur admiration, emulation, aspiration, empathy, and developmental advantages. Here, Ninivaggi offers a theory of envy and explores various ideas and concepts related to it. He proposes research paradigms for testability, advances principles and guidelines for pragmatic applications in psychotherapies and psychoeducation, and considers new paths for further discovery"--Provided by publisher.